ผลกระทบของการดำเนินนโยบายการคลังต่อตัวแปรทางเศรษฐกิจมหภาคของประเทศไทย - วรรณภา ร้องกาศ (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
This study aims to analyze the impact of fiscal policy on the macroeconomic variables of the Thai economy namely umemployment rate, interest rate, and Consumer Price Index. The data used here is a quarterly time series data during 2002:Q1 to 2012:Q4, covering 44 quarters. The data are estimated by the simultaneous equations model with three stage least squares (3SLS) The results of unit root test by Augmented Dickey - Fuller (ADF) found that all the variables used in the study are stationary at the level. According to the results of the impact of fiscal policy on macroeconomic variables, tax revenues have a positive effect to private consumption, private investment, government spending, unemployment rate and consumer price index. Where as, the increase of tax revenues, 1 percent impact on variables such increase of 0.655, 0.574, 0.937, 0.620, and 0.086, respectively. While government spending has a negative effect to unemployment rate. Moreover, the multiplier value of government spending is found to be 1.392. It directly stimulates economic growth and gross domestic product. This cause economic expantion and unemployment rate fell. In addition, total public debt has a negative effect to the private consumption and its multiplier value is found to be 0.368. The government debt, known as public debt, is the around of money which borrow from the preple in their country in order to increase a government expense. Consequently, The reverue of these people, who lend to the government money, will decrease and thereby increasing in gross domestic product.